Complete Penoscrotal Transposition with Other Extragenital Anomalies in a Neonate Delivered at Term - Ali Mahamudu Ayamba; Raymond Saa-Eru Maalman; Yaw Otchere Donkor; John Noah Anyorigiya (Case Reports in Urology)
A complete penoscrotal transposition (CPST) is a very uncommon congenital maldevelopment that is always associated with other abnormal body variations (malformations). We report a rare case of a term neonate delivered with CPST, which had a flaccid penis and an intact scrotum with unilateral limb and digital deformity, imperforate anus, cardiac malformation a facial deformity. Neonate died two hours after delivery. The foetal abnormality was not detected through routine antenatal services received by the mother.